2020
DOI: 10.1108/bij-05-2020-0225
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance in manufacturing companies: a benchmarking study

Abstract: PurposeThis study aims to explore manufacturing companies' environmental performance with the green supply chain management (GSCM) approach, taking into account company size, geographic region, industrial sector, target market and environmental management maturity level.Design/methodology/approachBased on the literature review, five propositions were put forward. An empirical study, using survey research, was completed. The survey questionnaire was designed with 46 items, using both the literature and industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
0
7
0
2
Order By: Relevance
“…However, it is important to emphasize that support from top management or supervisors is very integral if the implementation of IEM will yield its anticipated positive outcomes (Amin et al, 2020). Manifold studies have emphasized the existence and importance of environmental management in various area, spanning from the manufacturing industry (Trujillo-Gallego et al, 2020;Li et al, 2020), service industry (Lucas and Wilson, 2008;Fawehinmi et al, 2020) and mining industry (Kusi-Sarpong et al, 2016).…”
Section: Internal Environmental Management (Iem)mentioning
confidence: 99%
“…However, it is important to emphasize that support from top management or supervisors is very integral if the implementation of IEM will yield its anticipated positive outcomes (Amin et al, 2020). Manifold studies have emphasized the existence and importance of environmental management in various area, spanning from the manufacturing industry (Trujillo-Gallego et al, 2020;Li et al, 2020), service industry (Lucas and Wilson, 2008;Fawehinmi et al, 2020) and mining industry (Kusi-Sarpong et al, 2016).…”
Section: Internal Environmental Management (Iem)mentioning
confidence: 99%
“…Environmental deterioration and degradation issues recently become a significant concern in various parts of the world, including developing countries (Masri and Jaaron, 2017;Masron & Subramaniam, 2019;Asif et al, 2020). Manufacturing irresponsible practices in developing countries make the problem bigger (Ferronato and Torretta, 2019;Trujillo-Gallego et al, 2020;Karuppiah et al, 2020). This is resembled by common J o u r n a l P r e -p r o o f unsustainable management of manufacturing wastewater, open dumping and burning of solid waste, use of toxic substances, and uncontrolled pollutant emissions that harm the atmosphere (Ramayah et al, 2013;Namagembe et al, 2019;Ferronato and Torretta, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Laari et al (2016) suggested an investigation of GSCM activities with environmental sustainability since they could boost firms' environmental and financial performances. GSCM practices cover most initiatives to control the negative impacts of a company's products on the environment, while environmental performance measures the capability of a firm to control pollution, decrease waste, prevent utilize of hazardous substances and reduce environmental accidents (Trujillo-Gallego et al, 2020;Feng et al, 2018;Sahu et al, 2018;Çankaya and Sezen, 2019). GSCM practices positively affect the improvement of environmental performance by reducing the consumption of waste, minimizing the use of hazardous materials in production and improving the quality of the environment and community health.…”
Section: Environmental Management Practices (Emp)mentioning
confidence: 99%